Prenatal parabens exposure and infantile Eczema: Mediation by IL-17A, effect modification by breastfeeding, and evidence from network toxicology - Mengjun Chang; Xianjia Li; Ye Li; Yueyi Lv; Jin Ji; Can Liu; Guoai Yu; Xingyu Liao; Jie Gao; Leina Jia; Suzhen Guan (Environmental Pollution, 2026)

Advances in detection technologies for procymidone residues: From conventional methods to innovative approaches - Qiushuang Ai; Yifan Dong; Xiren Yu; Lijuan Yuan; Li Zhang; Mengjun Ye; Jianjun Xiang; Qiegen Liao; Jingtian Liang; Huming Shao; Dawen Zhang; Suyan Qiu (Food Control, 2026)

Hydrodesulfurization catalysts for ultra-clean diesel: Recent progress, modulation strategies, and emerging alternatives - Haihong Zhang; Chongchong Wu; Huiling Zhang; Ning Wang; Yu Song; Longnian Han; Siran Zhang; Mengjun Su; Jian Liu; Zhanggui Hou (Fuel, 2026)

No circadian variation of common vitamins and minerals levels in term human milk at first month postpartum - Mengjun Cui; Yipin Lyu; Jie Zhang; Renqiang Yu; Jianqiang Lai; Joe M. Regenstein; Peng Zhou (International Dairy Journal, 2026)

Design of structurally enhanced dual-network high internal phase emulsion gels for 3D-printable plant-based fat substitutes using carboxymethyl cellulose/heat-treated soy protein isolate and k-carrageenan - Yifei Liu; Yu Xia; Yiqiang Dai; Mengjun Sun; Xiudong Xia; Mingsheng Dong (Food Chemistry, 2026)

Spatiotemporal dynamics and heterogeneous driving mechanisms of soil wind erosion in the forest-grassland ecotone: Responses to climate change and vegetation dynamics across aridity types - Qiankun Yang; Zhiqing Jia; Xuequan Wang; Pingyi Zhou; Mengjun Zhong; Han Zhaorigetu; Yu shang (Journal of Environmental Management, 2025)

A rapid and ultrasensitive CRISPR/Cas12a-based assay for the accurate identification of T-even type phages - Chenhang Jiang; Yang Li; Ping Yu; Mengjun Fang; Di Huang; Xiangming Fang; Zhinan Xu (Biotechnology Letters, 2025)

Plant above-ground biomass drives the recovery of soil microbial communities in a subtropical-temperate transition zone following forest wildfire - Mengjun Hu; Jiayin Feng; Yu Shi; Pengshuai Shao; Zhijie Chen; Zhenxing Zhou; Jiali Wang (Applied Soil Ecology, 2025)

The chrononutrition of human milk: role of the circadian variation in human milk composition on sleep–wake regulation and brain development of infant - Mengjun Cui; Jie Zhang; Renqiang Yu; Jianqiang Lai; Peng Zhou (Current Opinion in Food Science, 2025)

Evodiamine encapsulated by hyaluronic acid modified zeolitic imidazolate framework-8 for tumor targeted therapy - Qiang Zhou; Dandan Xie; Kui Wang; Fengling Wang; Qiaoling Wang; Yue Huang; Mengjun Yu; Jingbin Huang; Yu Zhao (Drug Delivery and Translational Research, 2025)

Residue depletion and withdrawal time estimation of tilmicosin in black-bone silky fowls after administration via drinking water - Li Zhang; Lijuan Yuan; Mengjun Ye; Jianjun Xiang; Yifan Dong; Qiegen Liao; Suyan Qiu; Dawen Zhang; Xiren Yu (Food Additives & Contaminants: Part A, 2025)

Characterization and Correlation Analysis of Bacterial Composition and Physicochemical Quality in High- and Medium-Temperature Daqu from China’s Binzhou Region - Mengjun Cui; Wenchao Cai; Peirong Yu; Wei Chen; Chunhui Shan; Guo Zhuang; Yurong Wang (Current Microbiology, 2025)

Nanocluster-agminated amorphous cobalt nanofilms for highly selective electroreduction of nitrate to ammonia - Minghang Jiang; Mengfei Zhu; Junjie Ding; Huaizhu Wang; Qianchuan Yu; Xi Chen; Yi He; Mengjun Wang; Xiaojun Luo; Caijun Wu; Liyun Zhang; Xinghui Yao; et al. (Journal of Hazardous Materials, 2024)

Multi-Scale Higher-Order Dependencies (MSHOD): Higher-Order Interactions Mining and Key Nodes Identification for Global Liner Shipping Network - Yude Fu; Xiang Li; Jichao Li; Mengjun Yu; Xiongyi Lu; Qizi Huangpeng; Xiaojun Duan (Journal of Marine Science and Engineering, 2024)
Liner shipping accounts for over 80% of the global transportation volume, making substantial contributions to world trade and economic development. To advance global economic integration further, it is essential to link the flows of global liner shipping routes with the complex system of international trade, thereby supporting liner shipping as an effective framework for analyzing international trade and geopolitical trends. Traditional methods based on first-order global liner shipping networks, operating at a single scale, lack sufficient descriptive power for multi-variable sequential interactions and data representation accuracy among nodes. This paper proposes an effective methodology termed “Multi-Scale Higher-Order Dependencies (MSHOD)” that adeptly reveals the complexity of higher-order interactions among multi-scale nodes within the global liner shipping network. The key step of this method is to construct high-order dependency networks through multi-scale attributes. Based on the critical role of high-order interactions, a method for key node identification has been proposed. Experiments demonstrate that, compared to other methods, MSHOD can more effectively identify multi-scale nodes with regional dependencies. These nodes and their generated higher-order interactions could have transformative impacts on the network’s flow and stability. Therefore, by integrating multi-scale analysis methods to mine high-order interactions and identify key nodes with regional dependencies, this approach provides robust insights for assessing policy implementation effects, preventing unforeseen incidents, and revealing regional dual-circulation economic models, thereby contributing to strategies for global, stable development.

The potential benefits and mechanisms of protein nutritional intervention on bone health improvement - Yonghui Yu; Xinping Li; Mengjun Zheng; Linyue Zhou; Jingjie Zhang; Jing Wang; Baoguo Sun (Critical Reviews in Food Science and Nutrition, 2024)

Two mutations on S2 subunit were critical for Vero cell tropism expansion of infectious bronchitis virus HV80 - Yi Jiang; Xu Cheng; Mingyan Gao; Yan Yu; Xinhong Dou; Haiyu Shen; Mengjun Tang; Sheng Zhou; Daxin Peng (Veterinary Microbiology, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

Deciphering the evolving trajectories of China's megaregions from 1992 to 2020: A novel morphological approach based on global land cover products - Haojie Cao; Yu Li; Min Weng; Shiliang Su; Mengjun Kang (Applied Geography, 2024)

Treatment of Water Inrush in Mine Engineering Using a Superabsorbent Polymer: A Case Study of a Limestone Mine, Pingnan, China - Chenyang Ma; Yu’an Gong; Mengjun Chen; Rentai Liu; Jiwen Bai; Zhuo Zheng; Mengmeng Zhou (Mine Water and the Environment, 2023)

Evolution of Asian drying since 30 Ma revealed by clay minerals record in the West Pacific and its tectonic-climatic forcing - Yi Tang; Shiming Wan; Debo Zhao; Zhaojie Yu; Zhaokai Xu; Jin Zhang; Zehua Song; Mengjun Li; Hualong Jin; Wenjun Jiao; Hongkun Dong; Anchun Li (Science China Earth Sciences, 2023)

Adaptation of the infectious bronchitis virus H120 vaccine strain to Vero cell lines - Yi Jiang; Mei Xue; Mengjun Tang; Di Zhang; Yan Yu; Sheng Zhou (Veterinary Microbiology, 2023)

Evolution of silicate weathering in South China since 30 Ma: Controlling factors and global implications - Hualong Jin; Shiming Wan; Chang Liu; Debo Zhao; Wenqiang Pei; Zhaojie Yu; Jin Zhang; Zehua Song; Mengjun Li; Yi Tang; Anchun Li (Global and Planetary Change, 2023)

Enhanced weathering input from South Asia to the Indian Ocean since the late Eocene - Zehua Song; Shiming Wan; Christophe Colin; Christian France-Lanord; Zhaojie Yu; Arnaud Dapoigny; Hualong Jin; Mengjun Li; Jin Zhang; Debo Zhao; Xuefa Shi; Anchun Li (Science Bulletin, 2023)

Isolation and identification of a Bacillus subtilis HZ-72 exhibiting biocontrol activity against flax seedling blight - Taimeng Tan; Jiuxiang Zhu; Airong Shen; Jilie Li; Yongting Yu; Mengjun Zhang; Mengrui Zhao; Zhimin Li; Jia Chen; Chunsheng Gao; Yi Cheng; Litao Guo; et al. (European Journal of Plant Pathology, 2019)

Association of obesity and overweight with overall survival in colorectal cancer patients: a meta-analysis of 29 studies - Shuangjie Wu; Jun Liu; Xinhai Wang; Mengjun Li; Yu Gan; Yifan Tang (Cancer Causes & Control, 2014)